The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1044/2021_ajslp-20-00248
|View full text |Cite
|
Sign up to set email alerts
|

Self-Report and Caregiver Proxy-Report Agreement of Perceived Chronic Stress and Mutuality in Poststroke Aphasia

Abstract: Background People with aphasia (PWA) report higher levels of stress in comparison to stroke survivors without aphasia. If untreated, chronic stress is known to have detrimental effects to the body and brain and can negatively impact health and well-being. According to extant literature, self- and proxy-report agreement on objective domains is higher than on subjective domains, like chronic stress. In addition, high levels of mutuality, also known as shared feelings between two people, have been str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The most frequently used version of the scale was the PSS-10, found in 7 studies 2,19–24 . The PSS-14 was used less often, followed by the PSS-4 and the modified PSS 3,25–29 . Many studies (9) reported on the type and location of stroke (ie, descriptors including ischemic, hemorrhagic, left hemispheric, or right hemispheric stroke).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most frequently used version of the scale was the PSS-10, found in 7 studies 2,19–24 . The PSS-14 was used less often, followed by the PSS-4 and the modified PSS 3,25–29 . Many studies (9) reported on the type and location of stroke (ie, descriptors including ischemic, hemorrhagic, left hemispheric, or right hemispheric stroke).…”
Section: Resultsmentioning
confidence: 99%
“…The PSS was collected at multiple time points across studies. In cross-sectional studies, collection varied from time of hospital admission to 7 days after stroke, a few months, or even 12 months or greater post stroke 2,3,19,20,25–28 . These studies reported moderate to high levels of PS, ranging from 5.0 for the PSS-4, 14.04 to 16.90 for the PSS-10, and 29.62 for the PSS-14 2,3,19,20,26,28 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations